El Misal Romano reflexión sobre el lenguaje - Agrelo Martínez, Santiago 1942- (2020)
Durante siglos, en las comunidades eclesiales de rito romano, el pueblo fiel fue sujeto pasivo de celebraciones litúrgicas en las que estaba obligado a participar y de las que sólo el clero era reconocido como sujeto activo., Durante siglos, la celebración eucarística fue evidencia de un mundo de realidades sagradas personas y cosas- al que pertenecen algunos fieles y del que quedan fuera todos los demás. Durante muchos siglos, la autoridad eclesiástica reconocida como única autoridad competente sobre los libros litúrgicos, ha mantenido a los laicos en una condición de manifiesta inferioridad respecto de los clérigos, en una condición de obligada pasividad respecto de la celebración litúrgica, en una condición de indeseada ignorancia respecto de sus derechos y de sus deberes en la comunidad eclesia.
For centuries, in the ecclesial communities of the Roman rite, the faithful were the passive subjects of liturgical celebrations in which they were obliged to participate and in which only the clergy were recognized as active subjects. For centuries, the Eucharistic celebration was evidence of a world of sacred realities-persons and things-to which some of the faithful belong and from which all others remain outside. For many centuries, the ecclesiastical authority recognized as the only competent authority over liturgical books has kept the laity in a condition of manifest inferiority to the clergy, in a condition of obligatory passivity with regard to the liturgical celebration, in a condition of unwanted ignorance of their rights and duties in the ecclesial community., This confession must be followed by a necessary purpose of the amendment, which calls for a profound reform of the liturgical books, especially the Roman Missal.